2018
DOI: 10.2217/pgs-2017-0198
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Polymorphism and Haplotype Associate with Crisis Pain in Sickle Cell Disease

Abstract: We identified that rs920829 (incident rate ratio = 1.44, p = 0.027 additive; IRR=1.68, p=0.008 recessive models of negative binomial regression) and the CGAGG haplotype of TRPA1 (odds ratio = 0.218, p = 0.009) were significantly associated with utilization rate, suggesting that TRPA1 gene polymorphisms may influence acute pain crisis in SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…These results are similar to those found in a study of 132 African-American individuals, whose participants ranged in age from 15 -70 years, with a mean age of 34.2 years. (18) In another study, in the USA, with 542 adults (18 -84 years), the mean age was 32 years. (17) In the United Kingdom, a higher average was observed; 32 years in cases of HbSS; and 39 years for HbSC.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These results are similar to those found in a study of 132 African-American individuals, whose participants ranged in age from 15 -70 years, with a mean age of 34.2 years. (18) In another study, in the USA, with 542 adults (18 -84 years), the mean age was 32 years. (17) In the United Kingdom, a higher average was observed; 32 years in cases of HbSS; and 39 years for HbSC.…”
Section: Discussionmentioning
confidence: 96%
“…In a sample of 542 patients receiving care in North Carolina, USA, 427 (78.8%) had HbSS; 70 (12.9%), HbSC; 23 (4.2%), Sβ + ; and 22 (4.1%), Sβ 0 . (17)(18)(19)(20) In Chicago, USA, HbSS corresponded to 102 (77%) patients, followed by 15 cases (11.45%) HbSC, and 15 (11.45) with other variants. (15) At King's College Hospital, London, UK, 712 patients were observed for 10 years (2004-2013); there were 444 (62%) with HbSS; 229 (32%) with HbSC; 33 (5%) with HbSβ + ; and 6 (1%) with HbSβ 0 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with patients with the major homozygous GG genotype, those with the minor homozygous AA and heterozygous AG genotypes reported higher rates of acute pain. Moreover, in sickle cell patients, the GCAGG haplotype that contains the rs920829 G allele and rs1025928 C allele is associated with greater utilization of emergency departments and/or acute care centers for pain crisis [58]. In the same sample, study participants with the minor G allele of the TRPV1 rs222747 polymorphism showed a trend for decreased pain measured by the composite pain index (CPI) [58].…”
Section: Trp Genetic Variability and Painmentioning
confidence: 98%
“…For candidate SNP genotyping, DNA from blood and buccal swab samples were initially extracted as described in prior studies [23,30,31]. The QuickGene DNA whole blood extraction kit (AutoGen, MA, USA) or a salting-out approach adopted from Miller et al was used for DNA isolation from blood [32].…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%